PSA screening and prostate cancer mortality - Perron, Linda (2002)
BACKGROUND: Physicians have speculated that prostate-specific antigen (PSA) screening may be responsible for the reduction in prostate cancer mortality observed in the late 1990s. In order to test this hypothesis, we assessed the relation between the change in prostate cancer incidence in the early 1990s, attributed largely to PSA screening, and the subsequent change in prostate cancer mortality. METHODS: We divided the adult male population of Quebec aged 50 years and more into 15 birth cohorts. For each birth cohort, we computed the change in prostate cancer incidence between 1989 and 1993 and the change in prostate cancer mortality between 1995 and 1999. We then assessed the correlation between the changes in prostate cancer incidence and the subsequent changes in prostate cancer mortality by weighted linear regression. We also split up the study population into 15 regional populations and repeated the analysis described above. RESULTS: We found that even though most birth cohorts showed an increase in prostate cancer incidence and a subsequent decrease in mortality, the sizes of these changes were not inversely correlated (Pearson's r = 0.33, 1-sided p = 0.89). Similarly, in the regional population study, we found that a greater increase in prostate cancer incidence did not indicate a greater decline in mortality (Pearson's r = 0.13, 1-sided p = 0.68). INTERPRETATION: These results suggest that for our study population PSA screening was not associated with, and therefore cannot explain, the decline in prostate cancer mortality.